PECULIARITIES OF THE ARTISTIC IMAGE IN LINGUOPOETICS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article is devoted to the study of the concept of “artistic image” within the framework of the science of linguapoetics. The structure, functions and role of the artistic image in the artistic text are comprehensively analyzed. The article examines the use of a comprehensive methodology in conducting linguapoetic analysis of an artistic image, the role of stylistic and expressive means in a literary text. In addition, the article classifies the main levels of linguapoetic analysis and clearly demonstrates its scientific foundations using the works of famous scientists as an example.
Keywords: philology, linguistics, linguopoetics, stylistics, fiction, literary image, language units, level of linguopoetical analysis, language, aesthetics.